Synthesis, Characterization of Chitosan para- hydroxyl Benzaldehyde Schiff Base Linked Maleic Anhydride and the Evaluation of Its Antimicrobial Activities (Baghdad Science Journal, 2022)
Current research included preparation, characterization of some new chitosan- hydroxy benzaldehyde-Schiff bases with maleic anhydride. The present study aimed to the synthesis and characterization of novel chitosan Schiff base compounds using para- hydroxy benzaldeh and maleic anhydride. The  derivative of the  schiff-chitosan base, which is associated with different drugs, has been replaced with   different  amino  and  hydroxy  drugs.  The derivative is characterized by different analytical techniques. The results of FT-IR studies clearly indicate construction of the chief amine group in chitosan and the emergence of new bands that correspond to the association of maleic anhydride with the chitosan base. TGA, 1H-NMR, biological studies acquired two types of bacteria Gram +ve (Bacillus, Staphylococcus aureus)  and two bacteria Gram -ve (Escherichia coli, Pseudomonas aeruginosa) and yeast  like fungi (Candida albicans).